Study of Computational Theory of Surface Plasmon Resonance (SPR) for Porcine Gelatin Detected Sensor Based Nanomaterial Fe3O4–CNT in Otto’s Configuration - Lutfiyah, Maulina; Melati, Asih (Proceeding International Conference on Science and Engineering, 2017)
Accurate biomolecular detection can be performed through the Surface Plasmon Resonance (SPR) phenomenon. This study was conducted to determine the effect of the addition of Fe3O4 and Carbon Nanotube (CNT) nanomaterials in the Otto configurations and their use as porcine detection sensors. The research was conducted theoretically by finding the equation of reflectance and computationally using Matlab software version 7.12.0 to know SPR angle and reflectance value. This research uses ATR method with Otto configuration. The modeling was finished using HeNe laser light on 632.8 nm wavelength, semi-circle prism type BK7, metal layer of gold nanoparticles. The results of the research can be used in the detection of porcine gelatin by Otto configurations. The best air gap thickness is 30 nm. The best thickness of the gold layer and Fe3O4 layer are 50 nm and 0.05 nm. The applied of MWCNT nanoparticles is not effective in the detection of biomolecules based SPR. While the thickness of SWCNT used is 1 nm. The SWCNT material also proved to be better used in SPR systems. The addition of porcine gelatin layer in the system shows a graphic change in the form of increasing reflectance value and SPR angular shift.